Adsorption of Cu2+ by modified chitosan microspheres and its application in homocoupling of arylboronic acid - Kewang Zheng; Qiao Lin Ren; Ruixin Mo; Xiaofeng Deng; Baiyang Sun; Wei Wang; Zufeng Xiao; Caiqin Qin (Arabian Journal of Chemistry, 2022)
The CC bond coupling reactions have a wide range of applications in the synthesis of natural substances and the synthesis of physiologically active compounds. We first prepared modified chitosan microspheres by emulsification and investigated the performance of the chitosan adsorbent for the adsorption of copper ions. We then evaluated the catalytic performance of chitosan-supported copper microspheres in the self-coupling of arylboronic acids using 4-methoxybenzene as the model substrate, while exploring a wide range of substrates including aryl boronic acid derivatives and heterocyclic arylboronic acids, including aldehyde, nitro, and aldehyde groups. The experimental results show that good to excellent yields (55%-95%) of the desired dimer products were obtained under mild conditions at room temperature and in air, and the catalytic material could be reused up to five times with no significant decrease in catalytic activity.